PEMBAYARAN PAJAK TERTUNDA TERHADAP PAJAK BUMI DAN BANGUNAN MENURUT PERATURAN DAERAH KOTA SAMARINDA NOMOR 4 TAHUN 2011 TENTANG PAJAK DAERAH - Heseykiel Heseykiel (Universitas 17 Agustus 1945 Samarinda, 2019)
ABSTRACTRegional Income Agency in the discharge of his duties in order to improve the realization of the Earth and building Tax in accordance with the General conditions of taxation and can socialize with the people/Taxpayers in the process of tax payment delayed or payable taxes in accordance with applicable local Samarinda number 4 year 2011 about tax areas. In accordance with the data obtained from the Agency's Regional Income the city of Samarinda tax earnings from year to year is not yet realized optimally. Product realization of payment acceptance receivables against receivables in 2007 up to the year 2017 experienced ups and downs.The writing is aimed at knowing the process of settlement of the pending tax payments against the Earth and building Tax in accordance with the regulations and to know sanctions for Taxpayers in tax payments of Earth and Building pending in the Body Regional Income Samarinda.Research results are obtained, the process of tax payment is pending against the Earth and building Tax according to the applicable local Samarinda number 4 Year 2011 About tax areas have already done well. Where Taxpayers can take care of the certificate or letter to delay tax payments in debt. But close to the realization of the Earth and building tax payment has not yet been realized well and sanctions for Taxpayers in terms of payment of taxes Tax Earth and delayed Building is already a strict sanctions, penalties, which is given to the Compulsory Tax if it does not do payable tax payment will be charged an administrative sanction in the form of an interest rate of 2% (two percent) if the tax payable is not or less pay, article 88 paragraph (1) of the regulation of the regional city of Samarinda number 4 Year 2011 about taxes The area that the Taxpayer, because of negligence does not deliver the notice of tax areas or fill with incorrect or incomplete or incorrect information to attach to the detriment of the financial areas are convicted of confinement the longest one (1) year or criminal fines of as much as 2 (two) times the amount of tax payable that is not or less pay. Keyword: Delayed tax, Earth and building Tax